1981
DOI: 10.1002/ana.410100606
|View full text |Cite
|
Sign up to set email alerts
|

Resetting of tremor by mechanical perturbations: A comparison of essential tremor and parkinsonian tremor

Abstract: With the use of a computer-controlled torque motor, experiments were carried out on 11 patients with essential tremor and 13 with parkinsonian tremor to determine the effect of mechanical displacements at the wrist joint on the established pattern of tremor. Analysis of the timing of tremor bursts in electromyographic recordings before and following the stimuli revealed that the phase of essential tremor could be readily reset by external perturbations. In the majority of the parkinsonian patients the same typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…to modify the basic parameters of tremor, i.e., amplitude f 10], phase [11], and frequency [12]. This work demonstrated that most observed phenomena could by generally explained in terms of interactive models, but which specific mecha nisms were consistent with the present data?…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…to modify the basic parameters of tremor, i.e., amplitude f 10], phase [11], and frequency [12]. This work demonstrated that most observed phenomena could by generally explained in terms of interactive models, but which specific mecha nisms were consistent with the present data?…”
Section: Discussionsupporting
confidence: 79%
“…This work demonstrated that most observed phenomena could by generally explained in terms of interactive models, but which specific mecha nisms were consistent with the present data? Some re searchers have previously suggested various physiological mechanisms that may be implicated here [5,11 ], but since our data do not appertain to such mechanisms, we, like Rack and Ross [12], shall discuss this in systemic, rather than physiological, terms.…”
Section: Discussionmentioning
confidence: 83%
“…It is generally believed that Parkinsonian and cerebellar tremors often depend upon rhythmic activity generated within the CNS (for review see Marsden, 1984), though an interaction with spinally mediated stretch reflexes is frequently mooted (e.g. Lee & Stein, 1981;Marsden, 1984;Rack & Ross, 1986). Our data show that in principle a very active stretch reflex loop could oscillate autonomously in the frequency range 3-8 Hz.…”
Section: Relationship To Pathological Tremorsmentioning
confidence: 60%
“…Tremor amplitude and phase are susceptible to limb perturbations (Lee and Stein, 1981;Elble et al, 1992). Moreover, tremor may worsen after peripheral nerve damage, e.g., in paraproteinaemic/inflammatory neuropathies (Saifee et al, 2013).…”
Section: Tremor Onset Before Thalamomuscular Coherencementioning
confidence: 99%